The Effect of Weaving Activities on Fine Motor Skills of Group B Children at Permata Hati Playground - Nadzilah, Aulia; Andika, Windi Dwi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to see the effect of weaving activities on the fine motor skills of group B children at KB Permata Hati Ogan Ilir. The type of research is a pre-experimental method with a One Shoot Case Study Design. . The sampling technique used purposive sampling considering the low fine motor skills of children. The research sample consisted of 16 children. Data collection techniques included observation, testing, and documentation. Data were analyzed using the t-test, obtaining a calculated t value1.8 ≥ t table1.75 with α = 0.05 and dk = 15, so H0 is rejected and Ha is accepted. These results indicate that weaving activities have a positive influence on children's fine motor skills.